Efficacy of synthetic and biological DMARDs: a systematic literature review informing the 2022 update of the EULAR recommendations for the management of rheumatoid arthritis - Kerschbaumer, Andreas; Sepriano, Alexandre; Bergstra, Sytske Anne; Smolen, Josef S.; van der Heijde, Desiree; Caporali, Roberto; Edwards, Christopher John; Verschueren, Patrick; de Souza, Savia; Pope, Janet E.; Takeuchi, Tsutomu; Hyrich, Kimme L.; et al. (Annals of the Rheumatic Diseases, 2023)
OBJECTIVES: To update the evidence on efficacy of DMARDs (disease-modifying antirheumatic drugs) and inform the taskforce of the 2022 update of the European Alliance of Associations for Rheumatology (EULAR) recommendations for management of rheumatoid arthritis (RA). METHODS: This systematic literature review (SLR) investigated the efficacy of conventional synthetic (cs), biological (b), biosimilar and targeted synthetic (ts)DMARDs in patients with RA. Medline, EMBASE, Cochrane CENTRAL and Web of Science were used to identify all relevant articles published since the previous update in 2019 to 14 January 2022. RESULTS: Of 8969 search results, 169 articles were selected for detailed review and 47 were finally included. Trials investigated the efficacy of csDMARDs, bDMARDs and tsDMARDs, DMARD switching, tapering and trials investigating different treatment strategies. The compounds investigated were csDMARDs (methotrexate (MTX), leflunomide, sulfasalazine, hydroxychloroquine), bDMARDs (abatacept, adalimumab, certolizumab-pegol, denosumab, etanercept, infliximab, levilimab, olokizumab, opineracept, rituximab, sarilumab, tocilizumab) and tsDMARDs (baricitinib, filgotinib, tofacitinib, upadacitinib). The efficacy of csDMARDs+ short-term glucocorticoids in early RA was confirmed and similar to bDMARD+MTX combination therapy. Interleukin-6 pathway inhibition was effective in trials on olokizumab and levilimab. Janus kinase inhibitor (JAKi) was efficacious in different patient populations. After insufficient response to JAKi, patients could respond to TNFi treatment. Tapering of DMARDs was feasible for a proportion of patients, who were able to taper therapy while remaining in low disease activity or remission. CONCLUSION: The results of this SLR, together with one SLR on safety of DMARD and one on glucocorticoids, informed the taskforce of the 2022 update of the EULAR recommendations for pharmacological management of RA. sponsorship: The European Alliance of Associations for Rheumatology. (European Alliance of ...